ChemInform Abstract: Public‐Private Partnerships in Lead Discovery: Overview and Case Studies. Issue 45 (October 2016) - Gottwald, Matthias; Becker, Andreas; Bahr, Inke; Mueller‐Fahrnow, Anke
Abstract: Review: 25 refs.